Synthesis and characterization of egusi melon methyl ester as diesel fuel substitute - Giwa, Solomon Olanrewaju (2009)
Biodiesel is a monoalkyl esters of vegetable oils (VOs), animal fats and waste oil widely accepted as substitute for fossil-derived diesel fuel. It is a renewable and sustainable energy source that is environmentally friendly. Food-fuel strain of conventional VOs has renewed research interest in exploring 350 alternative oil-bearing crops that can be harnessed as diesel fuel substitute, but with less than 100 investigated. Colocynthis citrullus Lanatus, ‘egusi’, has been studied for the first time as a potential biodiesel feedstock. Crude oil from the seeds have been characterized and transesterified using methanol in the presence of sodium methoxide as catalyst. The design of experiment for the optimization of the reaction conditions was conducted using response surface methodology (RSM). A three-level-three-factors face centered central composite design was employed. Catalyst amount (0.25 - 1.8% wt.), reaction temperature (45 – 65 °C) and oil-methanol molar ratio (4 – 10) were studied as important factors influencing the reaction. Fuel properties of egusi melon methyl ester (EMME) were determined in accordance to ASTM D 6751 and EN 14214 standard test methods. The fatty acid profile of EMME was analyzed using gas chromatograph. Also, rheological behaviors of EMME and its blends (B2, B5, B10) in relation to viscosity were studied. The amount of catalyst and reaction temperature was the most significant (P < 0.0001) factors affecting the yield of EMME. Multiple regression analysis was used to develop an empirical mathematical model for predicting methyl ester yield of EMME. The optimum reaction conditions obtained from the model for EMME synthesis were 1:6.54 oil-to-methanol molar ratio, 1.22% catalyst amounts, and 65 ˚C reaction temperature resulting in a yield of 84.01%. Under experimental conditions, methyl esters yield of 84.46 ± 0.075% was obtained on an average with the optimal values. This yield value is well within the range predicted by the model. RSM was found to be a suitable technique for optimizing the transesterification of egusi melon seed oil. The quality and fuel properties of EMME determined were found to satisfy prescribed ASTM (D 6751) and EN 14214 specifications. The viscosity behavior of EMME and its blends with diesel fuel (pseudoplastic and Newtonian in nature) was found to agree with those of other biodiesels reported in literature. From this present study, it was discovered that fuel properties and fatty ester profile of egusi melon biodiesel resemble those of sunflower, soybean and safflower. The kinematic viscosity (KV) of EMME was found to be 3.51 mm2/s (at 40 °C), a value remarkably lower than most biodiesels (above 4.0 mm2/s at 40 °C) reported. In addition, its cloud point is relatively low compared to soybean, rapeseed and sunflower biodiesels. Comparisons of egusi melon biodiesel with Malaysian palm biodiesel were satisfactory with the former offering better cloud point and significantly lower KV than the latter. In this work, the probable potential of Colocynthis citrullus L. seed oil for biodiesel production is clearly presented.